Integrated terahertz optoelectronics - Liang, Guozhen (2018)
Currently, terahertz (THz) optical systems are based on bulky free-space optics. This is due to the lack of a common platform onto which different THz components, e.g., source, waveguide, modulator and detector, can be monolithically integrated. With the development of THz quantum cascade laser (QCL), it has been realized that the QCL chip may be such a platform for integrated THz photonics. Here, we report our recent works where the THz QCL is integrated with passive or optoelectronic components. They are: 1) integrated graphene modulator with THz QCL achieving 100% modulation depth and fast speed; 2) phase-locked THz QCL with integrated plasmonic waveguide and subwavelength antennas realizing dynamically widely tunable polarizations.